A new species of Megaselia Rondani (Diptera: Phoridae) associated with one sex of a dioecious fig tree in Thailand - Disney R. Henry L.; Compton Stephen G. (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2019)
Megaselia ischnopodae Disney n. sp. (Diptera, Phoridae) is reared from larvae found in mature male figs of Ficus ischnopoda Miq. (Urticales, Moracea) in Thailand. Other phorid species associated with fig trees are briefly reviewed.
24 cm
Keywords: scuttle flies; Agaonidae; Ficus ischnopoda; riparian forest; Oriental; Southest Asia

Four new species of Megaselia Rondani (Diptera: Phoridae) from France - Disney, R. Henry L.; Siffointe, René (Museum and Institute of Zoology, PAS, 2014)
Among Phoridae collected at Sallanches (France, Rhône-Alpes) are Megaselia marekdurskii Disney, previously only known from Poland, and the new species: M. betrugspinata Disney sp. n., M. museoconfluentis Disney sp. n., M. siffointei Disney sp. n. and M. similipropinqua Disney sp. n.
P. 47-55, ill. 25 cm
Bibliogr. p. 54-55
Abstarct in Polish
Keywords: Megaselia; Phoridae; phorid flies; phorids; scuttle flies; Brachycera; brachyceran flies; flies; Diptera; insects; Insecta; France; Rhône-Alpes; Sallanches; new species

Syrphid flies (Diptera, Syrphidae) from Mongolia collected by Polish expeditions - Bańkowska, Regina; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2000)
The paper contains a list of 18 species of dipterans of the family Syrphidae collected by Polish expeditions to central Mongolia. Among them Paragus compeditus WIED. and Eristalis abusiva COLL. are recorded from this area for the first time. Also a new species of Syrphidae – Paragus mongolicus sp. n. is described and illustrated.
Bibliogr. p. 53-54
P. 47-54 : ill. ; 24 cm
Abstarct in Polish. Taxa in Latin.
Keywords: Paragus mongolicus; Paragus; Eristalis abusive; holotype; Paragus compeditus; new taxa to the Mongolian fauna; new taxa; flies; insects; Insecta; hoverflies; flower flies; Syrphidae; syrphid flies; Brachycera; brachyceran flies; Diptera; new species; Mongolia

An annotated list of Tardigrada from Mts. Elbrus, Iran - Dastych, Hieronim (Państwowe Wydawnictwo Naukowe, 1972)
p. 47-54
Bibliogr.: p. 8
8 p. : ill. ; 25 cm
Abstract in Polish, Russian
Keywords: Tardigrada; moss piglets; tardigrades; waterbears; Iran; Elburs (mountains); Alborz; Albourz; Alburz; morphology

Ocena stanu biomasy listowia drzew - Cholewicka-Wiśniewska, Katarzyna (1952– ); Garbarczyk, Henryk (1947– ); Państwowe Wydawnictwo Naukowe (1951–1992); Polska Akademia Nauk. Instytut Zoologii (Państwowe Wydawnictwo Naukowe, 1981)
Liczbowanie stron również: P. 47-55
Bibliogr. p. 7-8 (53-54)
9 p. ; 24 cm
Abstract in Eng., Rus. Taxa in latin
Keywords: Poland; Warsaw; Białołęka Dworska; biomass; ecology; effect of human beings; man's impact

Two new species of Megaselia Rondani (Diptera: Phoridae) from Poland - Disney, R. Henry L.; Durska, Ewa (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2017)
Two new scuttle fly species of genus Megaselia are described from Poland. M. boguslawi sp. n. was found in central Poland in the pine forest after fire. M. wigryensis n. sp. was cought in the north-eastern part of country in the linden-oak-hornbeam forest of the Wigry National Park.
47-52 p. : ill. ; 24 cm
Keywords: Diptera; Phoridae; Megaselia; new species; Poland

Collembola of North Bull Island - new records for the Irish coast - Sterzyńska, Maria; Bolger, Thomas; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2004)
A study of the Collembola from the marine littoral habitats on North Bull Island, which is a nature Man and the Biosphere Nature Reserve in Ireland, revealed 43 species of which 9 are new to the Irish fauna. Several rare species, known only from a few localities in Europe, Willemia multilobata, Friesea cf. baltica, Protaphorura pseudocellata and Isotomodes sotoensiswere found.
Bibliogr. p. 50
P. 47-50 ; 25 cm
Abstarct in Polish. Taxa in Latin.
Keywords: littoral zone; supralittoral zone; geographical distribution; North Bull Island Nature Reserve; new taxa to the Irish fauna; Ireland; Entognatha; springtails (Collembola); collembolans; Collembola

First records of Myrmica vandeli Bondroit and M. tulinae Elmes, Radchenko et Aktaç (Hymenoptera: Formicidae) for Poland, with a key for the scabrinodis- and sabuleti-complexes - Radčenko, Aleksandr Grigor'evič (1955– ); Elmes, Graham W.; Czechowska, Wiesława (1947– ); Stankiewicz, Anna; Czechowski, Wojciech (1950– ); Sielezniew, Marcin; Polska Akademia Nauk. Muzeum i Instytut Zoologii (Museum and Institute of Zoology, PAS, 2003)
The first records from Poland of Myrmica vandeliand the recently described M. tulinae, both belonging to the scabrinodis-group,are reported. These species are poorly recorded and may be less rare than hitherto supposed. The current knowledge of their distributions and ecologies are summarised. The characteristic morphological features of the two species are illustrated and a key for separating them from their closest relatives in Poland is given.
Bibliogr. p. 56
P. 47-57 : ill. ; 25 cm
Abstarct in Polish. Taxa in Latin.
Keywords: Myrmica tulinae; Myrmica; sabuleti-complex; scabrinodis-complex; geographical distribution; classification; identification key; Poland; Sandomierska Forest; Krakowsko-Wieluńska Upland; insects; Insecta; Formicidae; ants; Hymenoptera; hymenopterans; new species to the Polish fauna; Myrmica vandeli

Predation of ants of the genus Formica L. (Hymenoptera, Formicidae) on Colorado beetles, Leptinotarsa decemlineata Say (Coleoptera, Chrysomelidae) - Godzińska, Ewa Joanna; Kieruzel, Maria; Korczyńska, Julita (Instytut Zoologii PAN, 1990)
W serii gł. nr 44
Bibliogr.p. 52-53
P. 47-53 : ill. ; 24 cm
Abstarct in Polish. Taxa in Latin
Keywords: insects; Insecta; feeding behaviour; Hymenoptera; ants; predatory insects; conferences; predators; ecology; Mazovian Lowland; congresses; Poland; Formicidae; beetles; hymenopterans; Coleoptera; Chrysomelidae; leaf beetles; adults; imagines; imago; larvae; Colorado potato beetle; Formica; behavioural defence; chemical defence; Leptinotarsa decemlineata

Small mammals in the diet of the tawny owl Strix aluco in selected sites of the Biebrza Basin and Knyszyn Forest in north-eastern Poland - Lesiński, Grzegorz; Błachowski, Grzegorz (Muzeum i Instytut Zoologii Polskiej Akademii Nauk, 2023)
The analysis of pellets of the tawny owl Strix aluco collected in the years 2009–2023 in 22 sites (ten in the Biebrza Basin and twelve in Knyszyn Forest) allowed for finding four species of Soricomorpha, nine species of Chiroptera and fifteen species of Rodentia (4, 5 and 12 in the Biebrza Basin and 4, 7 and 13 in Knyszyn Forest, respectively). Most common and most frequently caught by owls were: the bank vole Clethrionomys glareolus, the yellow-necked mouse Apodemus flavicollis and the common shrew Sorex araneus. Valuable species of bats included the pond bat Myotis dasycneme and the western barbastelle Barbastella barbastellus noted in Knyszyn Forest. Rare rodents found in both study areas were: the northern birch mouse Sicista betulina and the common dormouse Muscardinus avellanarius while the forest dormouse Dryomys nitedula was noted only in Knyszyn Forest. The European water vole Arvicola amphibius commonly noted in the Biebrza Basin was not found in Knyszyn Forest. On the contrary, the common pine vole Microtus subterraneus was reecorded only in Knyszyn Forest.
24 cm
Keywords: mammal fauna; Chiroptera; Rodentia; owl pellets; NE Poland